Structure Elucidation of Prenyl- and Geranyl-Substituted Coumarins in Gerbera piloselloides by NMR Spectroscopy, Electronic Circular Dichroism Calculations, and Single Crystal X-ray Crystallography - Tuo Li; Xue Ma; Daniil Fedotov; Louise Kjaerulff; Karla Frydenvang; Sonia Coriani; Paul Robert Hansen; Kenneth T. Kongstad; Dan Staerk (Molecules, 2020)
Crude ethyl acetate extract of Gerbera piloselloides (L.) Cass. was investigated by dual high-resolution PTP1B/α-glucosidase inhibition profiling and LC-PDA-HRMS. This indicated the presence of a series of unprecedented prenyl- and geranyl-substituted coumarin derivatives correlated with both α-glucosidase and PTP1B inhibitory activity. Repeated chromatographic separation targeting these compounds led to the isolation of 13 new compounds, of which ten could be isolated as both enantiomers after chiral separation. The structures of all isolated compounds were characterized by HRMS and extensive 1D and 2D NMR analysis. The absolute configurations of the isolated compounds were determined by comparison of experimental and calculated electronic circular dichroism spectra. Compound 6 features a rare furan-oxepane 5/7 ring system, possibly formed through addition of a geranyl unit to C-3 of 5-methylcoumarin, representing a new type of geranyl-substituted coumarin skeleton. Compounds 19 and 24 are the first examples of dimeric natural products consisting of both coumarin and chromone moieties.